RELASI PARADIGMATIK IKON KRISTIANI DALAM POSTER PROPAGANDA KUBA - Bima Wicandra, Obed (Nirmana, 2004)
Posters which are entitled Guerrilla Christ and Foreign Debt/IMF created by designers from Cuba contain many Christianity icons. Guerrilla Christ agitative poster with black and red colour background described Jesus Christ constricting a gun just looks like guerrillas. Foreign Debt/IMF poster described someone was crossed on the icon of US dollar as a symbol of IMF. As we know Cuba is one of the glorious communist socialist country. Writer is interested in investigating paradigm aspects related to the poster creating process include ideological aspect%2C community life%2C also narration or message extended. Abstract in Bahasa Indonesia : Poster yang berjudul Guerrilla Christ dan Foreign Debt/IMF karya desainer Alfredo Rostgaard dan Rafael Enriquez asal Kuba memasukkan ikon-ikon kristiani di dalamnya. Poster agitatif Guerrilla Christ dengan warna dasar hitam dan merah melukiskan gambar Yesus Kristus memanggul senjata layaknya seorang gerilyawan. Sedangkan poster Foreign Debt/IMF menggambarkan seorang yang disalib di atas ikon dollar AS sebagai simbol. Kuba merupakan salah satu negara sosialis komunis yang masih berjaya. Penulis tertarik untuk mengkaji lebih dalam mengenai unsur paradigmatik yang ada di sekeliling proses penciptaan poster tersebut%2C yaitu dari ideologi%2C kehidupan masyarakatnya hingga narasi atau pesan yang hendak disampaikan. Cuban Poster%2C Christianity Icons%2C Paradigm Relation.